Recent development in the preservation effect of lactic acid bacteria and essential oils on chicken and seafood products - Sharma, Heena; Fidan, Hafize; Özogul, Fatih; Rocha, João Miguel (Frontiers in Microbiology, 2022)
Chicken and sea foods are highly perishable owing to the higher moisture and unsaturated fatty acids content which makes them more prone to oxidation and microbial growth. In order to preserve the nutritional quality and extend the shelf-life of such products, consumers now prefer chemical free alternatives, such as lactic acid bacteria (LAB) and essential oils (EOs), which exert bio-preservative effect as antimicrobial and antioxidant compounds. This review will provide in-depth information about the properties and main mechanisms of oxidation and microbial spoilage in chicken and seafood. Further, basic chemistry and mode of action of LAB and EOs will be discussed to shed light on their successful application in chicken and seafood products. Metabolites of LAB and EOs, either alone or in the combination, inhibit or retard the lipid oxidation and microbial growth by virtue of their principal constituents and bioactive compounds including phenolic compounds, organic acids (lactic acid, propionic acid, acetic acid) and others. Therefore, application of LAB and EOs is widely recognized to extend the shelf-life of chicken and seafood products naturally without altering their functional and physicochemical properties. However, incorporation of any of these agents requires the optimization steps necessary to avoid the undesirable sensory changes. Besides, toxicity risks associated with EOs also demand the regularization of optimum dose for their inclusion in the products.